Coagulation sedimentation performance and model optimization of ultra-fine tailings overflow from hydrocyclone. (August 2022) - Niu, Fusheng; Zhang, Hongmei; Zhang, Jinxia; Yu, Xiaodong; Wang, Wanbo
Highlights: In this work, we believe that the three highlights of this manuscript will interest the general readers of your magazine. Firstly, the sedimentation rate of overflow superfine tailings under different flocculant dosage, pulp pH and temperature was studied. Secondly, the floc image is obtained by microscope, and the floc sample obtained by testing is processed by Image-Pro Plus software, and the floc particle size and its fractal dimension are obtained. Thirdly, the characteristics of flocculation and sedimentation of tailings particles are discussed. On the basis of the flocculation fractal fine tailings settlement model similar to the settlement curve in this study, the model was optimized according to the different settlement stages of the model, and the optimized settlement model was obtained. The optimization model is an accurate model, which can guide the operation of similar ultrafine mineral particles at different settling times. Abstract: In order to study the sedimentation characteristics of ultra-fine tailings overflow from hydrocyclone in a coagulation environment, the sedimentation velocity of overflow ultra-fine tailings under different coagulant dosage, pulp pH and temperature conditions were analyzed experimentally in this study. The results indicate that with the increase in sedimentation time, the sedimentation velocity of the coagulant first increases, followed by a decline before becoming flat. When the ferric chloride coagulant dosage is 90 mg/L, the pH of the pulp is 9. The sedimentation velocity reaches the maximum value of 5.57 mm/s, when the temperature of the pulp is 60 °C. According to the sedimentation process of the coagula, the coagulation sedimentation model of total tailings was extended and modified. The average absolute error between the corrected settlement velocity and the actual velocity was found as 0.0034, with the root mean square error is as 0.0088, which is relatively small. The results obtained from the theoretical calculations are consistent with the experimental data. The modified and optimized coagulation sedimentation model is important in promoting the theoretical research on the coagulation and sedimentation of such ultra-fine mineral particles.